Probing the Nuclear Equation of State with Peripheral Heavy Ion Collisions at Fermi Energies - Souliotis, G. A. (HNPS Advances in Nuclear Physics, 2020)
A systematic study of quasi-elastic and deep-inelastic collisions at Fermi energies is presented with the aim of obtaining insight into the underlying dynamics and the nuclear equation of state (EOS). Comparisons of experimental heavy-residue data to detailed calculations using the semiclassical microscopic model CoMD (Constrained Molecular Dynamics) are shown. The CoMD code implements an effective interac- tion with a nuclear-matter compressibility of K=200 (soft EOS) or K=380 (stiff EOS) with several forms of the density dependence of the nucleon-nucleon symmetry potential and imposes a constraint in the phase space occupation for each nucleon, restoring the Pauli principle during the collision. Preliminary results from these comparisons point to a soft equation of state (K=200) with a rather stiff density dependence of the isovector part (symmetry energy).